2014
DOI: 10.1158/0008-5472.can-14-0726
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Epithelial HuR Modulates Distinct Pathways of Proliferation and Apoptosis and Attenuates Small Intestinal and Colonic Tumor Development

Abstract: HuR is a ubiquitous nucleocytoplasmic RNA binding protein that exerts pleiotropic effects on cell growth and tumorigenesis. In this study, we explored the impact of conditional, tissue-specific genetic deletion of HuR on intestinal growth and tumorigenesis in mice. Mice lacking intestinal expression of HuR (Hur IKO mice) displayed reduced levels of cell proliferation in the small intestine and increased sensitivity to doxorubicin-induced acute intestinal injury, as evidenced by decreased villus height and a co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 46 publications
5
68
0
Order By: Relevance
“…Our previous studies in preclinical pancreatic cancer models (33)(34)(35)(36)(37)(38), as well as studies by others (17,19,20,24,(39)(40)(41), provided the rationale for investigating HuR inhibition in ovarian tumors We first established that suppression of HuR expression reduces proliferation, anchorage-independent growth, and invasion of ovarian cancer cells in vitro. We further demonstrate HuR inhibitionmediated reduction in tumor growth rate, delay in ascites development, and extension of lifespan by nearly 1.5-fold in two different ovarian cancer mouse models, a xenograft model and an orthotopic model in which mice bear tumors throughout the peritoneum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies in preclinical pancreatic cancer models (33)(34)(35)(36)(37)(38), as well as studies by others (17,19,20,24,(39)(40)(41), provided the rationale for investigating HuR inhibition in ovarian tumors We first established that suppression of HuR expression reduces proliferation, anchorage-independent growth, and invasion of ovarian cancer cells in vitro. We further demonstrate HuR inhibitionmediated reduction in tumor growth rate, delay in ascites development, and extension of lifespan by nearly 1.5-fold in two different ovarian cancer mouse models, a xenograft model and an orthotopic model in which mice bear tumors throughout the peritoneum.…”
Section: Discussionmentioning
confidence: 99%
“…The role of HuR in posttranscriptional regulation of multiple genes that promote survival of ovarian tumor cells provides an opportunity to develop an alternative strategy that targets multiple core signaling pathways at once. Indeed, proof-of-concept studies using HuR knockout mice and intracranial injection of mice with genetically silenced HuR primary glioblastoma cells have shown a reduction in colon tumor and glioblastoma growth, respectively (19,20). One approach to inhibit HuR is through targeted delivery of functional siRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Measure fecal bile acid output from stool (collected for 72 h from individually housed mouse) [15] if desired. This step is optional.…”
Section: Methodsmentioning
confidence: 99%
“…Determine bile acid pool size from total content of small intestine, gallbladder, and liver following sacrifice (optional) if desired [15]. …”
Section: Methodsmentioning
confidence: 99%
“…HuR is crucial for the maintenance of hematopoietic stem cells (27), the selection and chemotaxis of T cells (24), and B-cell development and activation/differentiation following an antigen encounter (28). Our previous study (29) and findings from others (30) have shown that conditional deletion of HuR in intestinal epithelial cells (IECs) inhibits mucosal growth in the small intestine and reduces tumor development by targeting multiple genes including the Wnt coreceptor Lrp6. Here, we study the role of HuR in the regulation of intestinal mucosal repair after acute injury and demonstrate that HuR enhances early epithelial restitution by activating translation of the mRNA that encodes the small GTP-binding protein Cdc42.…”
mentioning
confidence: 98%